##### Ads

related to: K.C

Congratz!!!! I am pretty good with the

**k**and**c**names so here let me give it a shot... (these can be spelled**C**...15 Answers · Pregnancy & Parenting · 30/01/2010

3N2(g)+6 H2O(g)⇌6 NO(g)+6 H2(g) K ' c = [NO(g)]^6 x [H2(g)]^6/{[N2(g)]^3 x [H2O(g)]^6...

1 Answers · Science & Mathematics · 19/04/2015

**K**= ab + (**c**/2) a = 3 b = 4**c**= 6**K**= (3)(4) + (6/2)**K**= 12 + 3**K**= 154 Answers · Science & Mathematics · 10/11/2010

...a "

**c**" and the next leter is "i" or "e" the "**c**" would sound like an "s", but if it is any other later it would sound like a "**k**": San Francisco= San Fransisko; the use of the...2 Answers · Entertainment & Music · 06/12/2012

1. For

**k**...**k**= (ln|y - 90| -**c**)/t**c**....**c**= ln|y - 90| - kt I don't get the initial values since you have more than two constants,**k**and**c**.2 Answers · Education & Reference · 12/09/2011

Ok. 273

**K**= 0**C**so therefore 330C = 330 + 273 = 603K**C**.5 Answers · Science & Mathematics · 21/06/2010

By the Binomial Theorem, (1 + x)^n = sum(

**k**=0 to n)**C**(n,**k**) x^**k**. Differentiating both sides twice, we get n(n - 1) (1 + x...1 Answers · Science & Mathematics · 19/10/2009

...28 +

**c c**= 6k - 10 12k = 28 + 6k - 10 6k = 18**k**= 3**c**= 6(3) - 10**c**= 8**k**+**c**= 3 + 8 = 111 Answers · Science & Mathematics · 11/01/2009

n *

**C**(n-1,**k**-1) = n * [(n-1)! / ((**k**-1)! (n-**k**)!)] = n! / ((**k**-1)! (n-**k**)!) =**k*** [n! / (**k**! (n-**k**)!)] =**k*****C**(n,**k**). I hope this helps!1 Answers · Science & Mathematics · 20/11/2011

ƒ( k ) = √[ k + ( k − c )^2], assuming c is a constant, and k is the only variable. ƒ...v, by chain rule, we get: ƒ'( k ) = u' ⋅ v ⋅ u^(v - 1) ƒ'( k ) = [1 + 2( k − c )] ⋅ 1/2 ⋅ [ k + ( k − c )^2]^(-1/2) ƒ'( k ) = (1 + 2k − 2c) / (2√[ k + ( k − c ...

3 Answers · Science & Mathematics · 23/02/2013

##### Ads

related to: K.C